Pronomina Bahasa Komering: Pronouns in The Komering Language - Rahmat Muhidin (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2020)
This research aims to describe personal pronouns, indifinite pronouns, and interrogative pronouns in Komering language. This research used descriptive method. The data were collected through listening, speaking, and instrospection method. The result of the research shaws that these are three pronouns in Komering language in the Baturaraja, Ogan Komering Ulu Regency: (1) personal pronouns, (2) indefinite pronouns, (3) interrogativa pronouns. Personal pronouns in Komering language are (a) first person singular, (b) first person plural, (c) second person singular, (d) second person plural, (e) third person singular, and (f) third person plural indefinite pronouns in Komering language are (a) common indifinite pronouns, (b) place indefinite pronouns, and (c) interpretation pronouns.